The effect of acupressure on cancer-related fatigue among school-aged children with acute lymphoblastic leukemia - Farideh Bastani; Maryam Khosravi; Leili Borimnejad; Negar Arbabi (Wolters Kluwer Medknow Publications, 2015)
Background: Fatigue is the most common side effect of chemotherapy in children with acute lymphoblastic leukemia (ALL). Acupressure is one of the most popular non-pharmacologic methods used to reduce fatigue in other settings. The aim of the study was to evaluate the effect of acupressure on reducing fatigue among children with ALL compared with a placebo treatment. Materials and Methods: In a single-blind, randomized, placebo-controlled clinical trial of 120 hospitalized school-aged children with ALL, 24 h after chemotherapy, they were randomly divided into experimental (n = 60) and placebo groups (n = 60). Intensity of fatigue was rated using the Visual Analog Scale. The intervention (finger acupressure) was applied on ST36 (true points) in the experimental group and on LI12 (sham points) in the placebo group. We evaluated the symptoms of fatigue intensity immediately and 1 h after intervention. Fatigue was also measured 24 h after intervention by Fatigue Scale-Child (FS-C). Data were analyzed by SPSS version 16.0 using descriptive statistics, independent t-test, and Chi-square and Fisher exact tests. Results: Significant differences were observed between the two groups in the intensity of fatigue 1 h after intervention (P < 0.001). But there was no significant difference between them regarding fatigue 24 h after intervention. Conclusions: Applying one time acupressure may reduce the intensity of fatigue at 1 h post-treatment. Therefore, acupressure could be recommended as an effective, non-pharmacologic method for some CRF control. Applying one time acupressure did not have a long-term effect.